Occupational Stress Coping Mechanisms and Work Performance Of Teachers - Bellin, Mary Divine Stephanie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the occupational stress coping mechanisms and work performance of public elementary school teachers in the Teresa Sub-Office during the School Year 2024–2025. The research aimed to determine the extent of coping strategies employed by teachers and their relationship to performance outcomes. The total population of 314 teachers from Abuyod, Bagumbayan, Quiterio San Jose, Pantay, Prinza, Sitio Ibabaw I, and Teresa Elementary Schools served as respondents. Data were collected using a descriptive survey research design through a researcher-made questionnaire checklist covering coping domains, including mindset and thinking patterns, managing feelings, action taken, body’s response, support system, and finding purpose and meaning. Documentary analysis of teachers’ Individual Performance Commitment and Review Forms (IPCRF) provided insights into their work performance.Findings revealed that the majority of teachers were mature-aged, predominantly female, married, holding a Teacher I position, and had obtained a master’s degree. Most had 6–15 years of service and attended various in-service trainings. Teachers reported a high extent of occupational stress coping mechanisms across all domains. Significant differences in coping mechanisms were observed based on educational attainment and position title, while other demographic variables such as age, sex, civil status, length of service, and in-service training were not significant. Work performance was generally Very Satisfactory, and statistical analysis indicated a positive relationship between coping mechanisms and work performance.The study concluded that enhancing teachers’ coping strategies positively influences their performance. It is recommended that school administrators design differentiated wellness and coping workshops, integrate stress management modules into training programs, and provide incentives for higher education pursuits. Further studies may explore additional factors affecting teachers’ coping strategies and performance.